(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This work, comprehensive work is carried out on improving the preschool education system, the development of children’s interests, talents, mental and physical characteristics. “...the implementation of such tasks as the introduction of modern educational programs and technologies that develop children comprehensively intellectually, spiritually-aesthetically and physically into the educational process, a radical increase in their level of school readiness.